Vesicular Drug Delivery Systems: Promising Approaches in Ocular Drug Delivery - Eslim Batur; Samet Özdemir; Meltem Ezgi Durgun; Yıldız Özsoy (MDPI AG, 2024)
Ocular drug delivery poses unique challenges due to the complex anatomical and physiological barriers of the eye. Conventional dosage forms often fail to achieve optimal therapeutic outcomes due to poor bioavailability, short retention time, and off-target effects. In recent years, vesicular drug delivery systems have emerged as promising solutions to address these challenges. Vesicular systems, such as liposome, niosome, ethosome, transfersome, and others (bilosome, transethosome, cubosome, proniosome, chitosome, terpesome, phytosome, discome, and spanlastics), offer several advantages for ocular drug delivery. These include improved drug bioavailability, prolonged retention time on the ocular surface, reduced systemic side effects, and protection of drugs from enzymatic degradation and dilution by tears. Moreover, vesicular formulations can be engineered for targeted delivery to specific ocular tissues or cells, enhancing therapeutic efficacy while minimizing off-target effects. They also enable the encapsulation of a wide range of drug molecules, including hydrophilic, hydrophobic, and macromolecular drugs, and the possibility of combination therapy by facilitating the co-delivery of multiple drugs. This review examines vesicular drug delivery systems, their advantages over conventional drug delivery systems, production techniques, and their applications in management of ocular diseases.